1999
DOI: 10.1128/mmbr.63.1.174-229.1999
|View full text |Cite
|
Sign up to set email alerts
|

Surface Proteins of Gram-Positive Bacteria and Mechanisms of Their Targeting to the Cell Wall Envelope

Abstract: SUMMARY The cell wall envelope of gram-positive bacteria is a macromolecular, exoskeletal organelle that is assembled and turned over at designated sites. The cell wall also functions as a surface organelle that allows gram-positive pathogens to interact with their environment, in particular the tissues of the infected host. All of these functions require that surface proteins and enzymes be properly targeted to the cell wall envelope. Two basic mechanisms, cell wall sorting and targeting, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
601
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,185 publications
(624 citation statements)
references
References 890 publications
(1,012 reference statements)
11
601
0
1
Order By: Relevance
“…It is widely accepted that the cell-wall-exposed proteins/ outer surfaces of pathogenic bacteria are of great importance to understanding their pathogenesis (Navarre & Schneewind, 1999;Cabanes et al, 2002). Not only are surface-associated components implicated in bacterial defense machineries but also they are involved in virulencerelated behaviors (e.g., adhesion) (Navarre & Schneewind, 1999;Maione et al, 2005). Thus, for vaccine development against pathogenic bacteria, current interest has shifted from the CPS antigen to surface proteins with robust immunogenicity (Navarre & Schneewind, 1999;Cabanes et al, 2002;Maione et al, 2005;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely accepted that the cell-wall-exposed proteins/ outer surfaces of pathogenic bacteria are of great importance to understanding their pathogenesis (Navarre & Schneewind, 1999;Cabanes et al, 2002). Not only are surface-associated components implicated in bacterial defense machineries but also they are involved in virulencerelated behaviors (e.g., adhesion) (Navarre & Schneewind, 1999;Maione et al, 2005). Thus, for vaccine development against pathogenic bacteria, current interest has shifted from the CPS antigen to surface proteins with robust immunogenicity (Navarre & Schneewind, 1999;Cabanes et al, 2002;Maione et al, 2005;Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Not only are surface-associated components implicated in bacterial defense machineries but also they are involved in virulencerelated behaviors (e.g., adhesion) (Navarre & Schneewind, 1999;Maione et al, 2005). Thus, for vaccine development against pathogenic bacteria, current interest has shifted from the CPS antigen to surface proteins with robust immunogenicity (Navarre & Schneewind, 1999;Cabanes et al, 2002;Maione et al, 2005;Li et al, 2006). Whole genome-wide screening was carried out to search for a universal Group B Streptococcus (GBS) vaccine (Maione et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic treatment with lysozyme has also been shown effective in lysing certain gram-positive species. 21,22 Upon lysozyme treatment, H. influenzae and S. aureus were detected across a range of concentrations of starting material ( Table 1). Whereas the S. aureus genome copy numbers being detected in the PLEX-ID platform were generally lower compared with H. influenzae, detection of the former organism was significantly improved after lysozyme treatment, including detection at 10 1 cfu of input material (Table 1), which was not achieved before lysozyme addition (data not shown).…”
Section: Enhancement Of Gram-positive Bacterial Dna Yieldmentioning
confidence: 99%
“…Common features of CWPs are an N-terminal signal peptide followed by a so-called A region or domain, segments of repeated domains and a characteristic C-terminal sorting signal. The sorting signal contains an important cell-wall-anchoring site or LPXTG motif, which covalently binds to the cell wall [10,11]. However, it has recently been shown that the collagen-binding adhesin Slr of Gram-positive Streptococcus pyogenes lacks the LPXTG motif, but uses a cell-wall-anchoring TLIA lipobox instead [12].…”
Section: Reviewmentioning
confidence: 99%